2017
DOI: 10.1016/j.drugalcdep.2017.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus and locomotor effects of para-substituted and benzofuran analogs of amphetamine

Abstract: Novel psychoactive substances have maintained a prominent role in the global drug culture, despite increased regulation by governing bodies. Novel compounds continue to become available on the market, often in "Ecstasy" or "Molly" formulations in lieu of MDMA, at a much faster rate than they can be properly characterized. The current study aimed to investigate the discriminative stimulus and locomotor effects of three putatively entactogenic compounds that have become increasingly prevalent on the drug market:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
4
12
0
Order By: Relevance
“…Other compounds with psychostimulant-like effects also decrease locomotor activity, although most of them (MDMA, flephedrone, MDAI, and DMAA) produce rebound stimulant effects later in the time course (Dolan and Gatch, 2015;Gatch et al, 2013;2016). 4-Fluoroamphetamine (4-FA) did produce depressant effects with little or no rebound stimulant effects (Dolan et al, 2017) similar to those produced by TH-PVP in the present study. None of these compounds are selectively dopaminergic, as MDMA and MDAI produce both serotonergically and dopaminergically mediated effects and DMAA produces its effects primarily through adrenergic receptors (Monte et al, 1993;Iversen et al, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Other compounds with psychostimulant-like effects also decrease locomotor activity, although most of them (MDMA, flephedrone, MDAI, and DMAA) produce rebound stimulant effects later in the time course (Dolan and Gatch, 2015;Gatch et al, 2013;2016). 4-Fluoroamphetamine (4-FA) did produce depressant effects with little or no rebound stimulant effects (Dolan et al, 2017) similar to those produced by TH-PVP in the present study. None of these compounds are selectively dopaminergic, as MDMA and MDAI produce both serotonergically and dopaminergically mediated effects and DMAA produces its effects primarily through adrenergic receptors (Monte et al, 1993;Iversen et al, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…However, given that response rate was similarly reduced in the discrimination studies as the locomotor studies, it seems feasible that comparable processes are occurring in both rats and mice. In addition, there are strong correlations between ED50s in the locomotor activity assay and the drug discrimination assay across psychostimulants (Carroll et al, 2009; Gatch et al, 2013; 2015; Katz et al, 2001) and other compounds with psychostimulant-like discriminative stimulus effects, such as the supplement dimethylamylamine (Dolan and Gatch, 2015), 4-fluoroamphetamine (Dolan et al, 2017), and MDAI (Gatch et al, 2016) also decrease locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study regarding the effects of the benzofurans 5‐APB and 6‐APDB on discriminative stimulus and behavior of rodents concluded that these drugs increase locomotor activity and fully substitute for MDMA, indicating that they might share an abuse pattern with this classic club drug (Dolan, Forster, & Gatch, ). Another recent work on the dependence liability of 5‐APB in rodents concluded that this benzofuran elicited increases in conditioned place preference but did not facilitate self‐administration, suggesting that 5‐APB has rewarding effects, rather than reinforcing effects (Cha et al, ).…”
Section: Subjective Effects In Humans and Other Biological Effectsmentioning
confidence: 99%
“…Both benzofurans elicited a time‐ and dose‐dependent stimulation of horizontal activity in the animals, with an increase in the duration of stimulation accompanying the dose increase from 1 mg/kg up to 10 mg/kg. A dose of 25 mg/kg caused the depression of activity and delayed the stimulant effect (Dolan et al, ). Therefore, it is possible to expect a significant influence over other pharmacodynamic effects.…”
Section: Influential Factors On Toxicodynamic Effectsmentioning
confidence: 99%